2014
DOI: 10.1021/es500152m
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Microcystin-LR-Induced Toxicity in Mouse Spermatogonia by miR-96

Abstract: Microcystin (MC)-LR is a cyclic heptapeptide that acts as a potent reproductive system toxin, especially by decreasing sperm quality through affecting spermatogonia. However, the molecular mechanisms of MC-induced spermatogonial cytotoxicity still remain unclear. The present study was designed to investigate changes in microRNA (miRNA) profiles and their potential functions in spermatogonia (GC-1 cell line) following treatment with MC-LR. With microarray analysis, 101 miRNAs were identified to be significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…Total protein was isolated from cells following various treatments. Western blot was applied according to a previous study (Zhou et al, 2014). Briefly, cells were washed three times with PBS and lysed in ice-cold extraction buffer (50 mM Tris-HCl pH 7.4, 150 mM NaCl, 1% NP, 0.1% SDS, and a 1× protease inhibitor cocktail).…”
Section: Methodsmentioning
confidence: 99%
“…Total protein was isolated from cells following various treatments. Western blot was applied according to a previous study (Zhou et al, 2014). Briefly, cells were washed three times with PBS and lysed in ice-cold extraction buffer (50 mM Tris-HCl pH 7.4, 150 mM NaCl, 1% NP, 0.1% SDS, and a 1× protease inhibitor cocktail).…”
Section: Methodsmentioning
confidence: 99%
“…The expression of 5 multispecific organic anion-transporting polypeptides (OATPs, -1a5, -3a1, -6b1, -6c1, and -6d1) was affected by MC-LR [68], especially OATP3a1, and Oatps may transport MC-LR into spermatogonia, resulting in cytotoxicity to the male reproductive system. With microarray analysis [69], 101 miRNAs were identified to be significantly altered in spermatogonia (GC-1 cells) treated with MC-LR, revealing an important link between miRNA and MC-LR in inducing reproductive toxicity. Inhibition of miR-96 may be one of the mechanisms for MC-induced sperm abnormality through regulating the expression of deleted-in azoospermia-associated protein 2 (DAZAP2).…”
Section: 2mentioning
confidence: 99%
“…These studies revealed that numerous genes and metabolic pathways involved in cytoskeleton assembly, oxidative stress, cell cycle regulation, and energetic metabolism were differentially regulated. Whilst most of these studies focused on the hepatotoxicity of MCs, only a few proteomic and microarray studies investigated the male reproductive toxicity in zebrafish testis [32], mouse spermatogonia [69] and Sertoli cells [74], respectively. Future work could better clarify the reproductive toxicological mechanism involved in MCs by the powerful 'omics' approaches.…”
Section: Application Of High-throughput Analytical Techniquesmentioning
confidence: 99%
“…Many studies have demonstrated the lethality of MC-LR on various cells including the human liver 7702 cells, rat testicular Sertoli cells and mouse spermatogonia (Chen et al, 2013; Sun et al, 2014; Zhou et al, 2014). Here, we found that exposure to 1~30 μM of MC-LR brought about inhibition of CHO cells growth.…”
Section: Discussionmentioning
confidence: 99%